2010
DOI: 10.1016/j.astropartphys.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of radio emission from air showers in atmospheric electric fields

Abstract: We study the effect of atmospheric electric fields on the radio pulse emitted by cosmic ray air showers. Under fair weather conditions the dominant part of the radio emission is driven by the geomagnetic field. When the shower charges are accelerated and deflected in an electric field additional radiation is emitted. We simulate this effect with the Monte Carlo code REAS2, using CORSIKA-simulated showers as input. In both codes a routine has been implemented that treats the effect of the electric field on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(40 reference statements)
1
10
0
2
Order By: Relevance
“…A simulation on the basis of (outdated) REAS2 simulations [150] confirmed that air showers can be influenced significantly by strong electric fields and that also the radio emission can be strongly changed. This means that radio emission from air showers in thunderstorms carries information on the electric fields that they propagated through.…”
Section: Influence Of Thunderstormsmentioning
confidence: 95%
“…A simulation on the basis of (outdated) REAS2 simulations [150] confirmed that air showers can be influenced significantly by strong electric fields and that also the radio emission can be strongly changed. This means that radio emission from air showers in thunderstorms carries information on the electric fields that they propagated through.…”
Section: Influence Of Thunderstormsmentioning
confidence: 95%
“…Like the geomagnetic field, the atmospheric electric field also accelerates electrons and positrons in opposite directions and induces time-variable transverse currents. During normal weather conditions the atmospheric field is a few 100 V/m and its force is negligible against the geomagnetic Lorentz force [172]. However, during rain the field can be significantly stronger, and during thunderstorms it can exceed several 10 kV/m.…”
Section: Atmospheric Electric Fieldmentioning
confidence: 99%
“…First measurements of the radio footprint of extensive air showers, made during periods where there were thunderstorms in the area, so-called thunderstorm conditions, have been reported by the LOPES [21,22] collaboration. It was seen that the amplitude of the radiation was strongly affected by the atmospheric electric fields [23]. More recently detailed measurements of the radio footprint, including its polarization were reported by the LO-FAR [24] collaboration.…”
Section: Introductionmentioning
confidence: 99%